Relationship between lower-lip fistulae and cleft lip and/or palate in Van der Woude syndrome - Onofre, Mirian Aparecida [UNESP]; Brosco, H. B.; Taga, R. (Decker Periodicals Inc, 1997)
Objective: This study was conducted to evaluate the relationship between fistulae of the lower lip and cleft lip and/or palate in patients with Van der Woude syndrome.Methods: the medical records of 11,000 patients with cleft lip and/or palate registered at the Cleft Lip-Palate Research and Rehabilitation Hospital, University of São Paulo, Bauru were reviewed. of these patients, 133 (1.2%) presented with Van der Woude syndrome.Results: of the 133 patients, 88 (66.2%) exhibited full clefts, 22 (16.5%) only cleft lip, and 23 (17.3%) only cleft palate. The lower-lip fistulae observed in these 133 patients were bilateral symmetric in 66 (49.7%), bilateral asymmetric in 42 (31.6%), microform in 19 (14.3%), median in 5 (3.8%), and unilateral in 1 (0.7%).Conclusion: This population sample appears to exhibit the previously published tendency for bilateral, unilateral, or mixed-type congenital fistulae to be associated with cleft lip with or without cleft palate, while so-called microforms or conic elevations are almost exclusively associated with cleft palate.
Keywords: cleft lip and/or palate; congenital fistulas of lower lip; Van der Woude syndrome